Carbon nitrides and metal nanoparticles: from controlled synthesis to design principles for improved photocatalysis. (20th September 2018) - Teixeira, Ivo F.; Barbosa, Eduardo C. M.; Tsang, Shik Chi Edman; Camargo, Pedro H. C.
Abstract : This review discusses synthetic strategies, photocatalytic applications, charge-transfer mechanisms, and design principles in hybrids composed of g-C3 N4 and metal nanoparticles. Abstract : The use of sunlight to drive chemical reactions via photocatalysis is of paramount importance towards a sustainable future. Among several photocatalysts, earth-abundant polymeric carbon nitride (PCN, often wrongly named g-C3 N4 ) has emerged as an attractive candidate due to its ability to absorb light efficiently in the visible and near-infrared ranges, chemical stability, non-toxicity, straightforward synthesis, and versatility as a platform for constructing hybrid materials. Especially, hybrids with metal nanoparticles offer the unique possibility of combining the catalytic, electronic, and optical properties of metal nanoparticles with PCN. Here, we provide a comprehensive overview of PCN materials and their hybrids, emphasizing heterostructures with metal nanoparticles. We focus on recent advances encompassing synthetic strategies, design principles, photocatalytic applications, and charge-transfer mechanisms. We also discuss how the localized surface plasmon resonance (LSPR) effect of some noble metals NPs ( e.g. Au, Ag, and Cu), bimetallic compositions, and even non-noble metals NPs ( e.g., Bi) synergistically contribute with PCN in light-driven transformations. Finally, we provide a perspective on the field, in which the understanding of the enhancement mechanisms combined with truly controlled synthesis can act as a powerful tool to the establishment of the design principles needed to take the field of photocatalysis with PCN to a new level, where the desired properties and performances can be planned in advance, and the target material synthesized accordingly.